Structural Analysis of One Class of Dynamical Systems - Koshlyakov, V. N.; Makarov, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We develop the method of structural transformations of dynamical systems (proposed earlier by Koshlyakov) for systems containing nonconservative positional structures. The method under consideration is based on structural transformations that enable one to eliminate nonconservative positional terms from the original system without changing its stability properties.